Non-symmetric Number Triangles Arising from Hypercomplex Function Theory in IR^{n+1} - Cação, Isabel (2022)
The paper is focused on intrinsic properties of a one parameter family of non-symmetric number triangles T(n), n ≥ 2, which arises in the construction of hyperholomorphic Appell polynomials.